THE INFLUENCE OF PERCEPTIONS OF PATIENTS' RIGHTS ON ORGANIZATIONAL COMMITMENT OF EMPLOYEES: A SURVEY ON PRIVATE HOSPITAL EMPLOYEES (Third Sector Social Economic Review, 2017)
This research addresses the concept of patient rights and organizational commitment and assesses the impact of patient rights enforcement on organizational commitment.  As a result of the literature survey on the subject, and based on theoretical explanations, it has been suggested that one of the determining factors of organizational commitment may be the importance that the institution places on patient rights. A survey was conducted on the administrative staff and health personnel working in the hospitals to determine the relationship between patient rights enforcement and organizational commitment. The purpose of this study is to examine the relation between the importance of the aimed institution to patient rights and the attitude of employees to organizational commitment. With this study, it was aimed to determine the effect of observing patient rights applications in hospitals on employee commitment. The sample of the research is the administrative and health personnel who are working in a special hospital chain in the province of Istanbul. Within the scope of the research, ""Patient Rights Scale"" of Aşkar (2006) and ""Organizational Commitment Scale"" adapted to Turkish by Boylu, Pelit and Güçer (2007) developed by Meyer and Allen (1997). According to the results obtained, there was a significant relationship between patient rights applications and employee commitment perception. It is thought that the service offered to the patient is trusting the institutions of employees with justice. As a result, the increase in institutional loyalty has been achieved. The results of the research included evaluations of health workers' commitment and patient rights enforcement.
Keywords: Patient Rights; Employee Commitment; Employee Satisfaction; Organizational commitment; Health Sector